Outcomes of comprehensive fixed appliance orthodontic treatment: A systematic review with meta-analysis and methodological overview - Papageorgiou, Spyridon N. (Korean J Orthod, 2017)
OBJECTIVE: The aim of this systematic review was to assess the occlusal outcome and duration of fixed orthodontic therapy from clinical trials in humans with the Objective Grading System (OGS) proposed by the American Board of Orthodontics. METHODS: Nine databases were searched up to October 2016 for prospective/retrospective clinical trials assessing the outcomes of orthodontic therapy with fixed appliances. After duplicate study selection, data extraction, and risk of bias assessment according to the Cochrane guidelines, random-effects meta-analyses of the mean OGS score and treatment duration were performed and 95% confidence intervals (CIs) were calculated. RESULTS: A total of 34 relevant clinical trials including 6,207 patients (40% male, 60% female; average age, 18.4 years) were identified. The average OGS score after treatment was 27.9 points (95% CI, 25.3–30.6 points), while the average treatment duration was 24.9 months (95% CI, 24.6–25.1 months). There was no significant association between occlusal outcome and treatment duration, while considerable heterogeneity was identified. In addition, orthodontic treatment involving extraction of four premolars appeared to have an important effect on both outcomes and duration of treatment. Finally, only 10 (39%) of the identified studies matched compared groups by initial malocclusion severity, although meta-epidemiological evidence suggested that matching may have significantly influenced their results. CONCLUSIONS: The findings from this systematic review suggest that the occlusal outcomes of fixed appliance treatment vary considerably, with no significant association between treatment outcomes and duration. Prospective matched clinical studies that use the OGS tool are needed to compare the effectiveness of orthodontic appliances.